2020
DOI: 10.3389/fvets.2020.585789
|View full text |Cite
|
Sign up to set email alerts
|

Possible Prophylactic Approach for SARS-CoV-2 Infection by Combination of Melatonin, Vitamin C and Zinc in Animals

Abstract: SARS-CoV-2, an epidemic, causes severe stress in both human and animals and may induce oxidative stress (OS) and increases susceptibility to infection. Domestic animals are found infected by their COVID-2 suffering owners. Chronic immobilization stress (CIS), a model of psychological and physical stress of confinement, can trigger depression and anxiety in animals. We evaluated the ameliorative effect of the proposed SARS-CoV-2 prophylactic drugs melatonin, vitamin C, and zinc on CIS-induced OS, inflammation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…It has anxiolytic, antidepressant, and sleeping effects, as well as the ability to reduce the consequences of stress [ 82 , 83 ]. The last is confirmed by an experimental study, where the combination of melatonin, vitamin C, and zinc was an effective preventive measure against severe psychological and chronic stress-induced biochemical manifestations of oxidative stress in rats due to abnormal conditions (e.g., SARS-CoV-2) [ 84 ]. According to a systematic review of 27 randomized controlled trials (involving 2319 participants), melatonin (doses varied from 3 to 10 mg per day) is more effective than a placebo in reducing anxiety.…”
Section: Anxiety Insomnia and Melatoninmentioning
confidence: 93%
“…It has anxiolytic, antidepressant, and sleeping effects, as well as the ability to reduce the consequences of stress [ 82 , 83 ]. The last is confirmed by an experimental study, where the combination of melatonin, vitamin C, and zinc was an effective preventive measure against severe psychological and chronic stress-induced biochemical manifestations of oxidative stress in rats due to abnormal conditions (e.g., SARS-CoV-2) [ 84 ]. According to a systematic review of 27 randomized controlled trials (involving 2319 participants), melatonin (doses varied from 3 to 10 mg per day) is more effective than a placebo in reducing anxiety.…”
Section: Anxiety Insomnia and Melatoninmentioning
confidence: 93%
“…This inhibition gradually weakened with time, since the degree of inhibition is negatively related with the dosage of melatonin. Melatonin may regulate the activation of T/B cells, playing a critical role in the regulation of immune balance Kim et al ( 2020 ) TLR4-deficient BALB/c mice Male (Not specified) 8–9 weeks Inflammatory bowel disease 10 mg/kg/day (i.p) Melatonin significantly increases goblet cells and Reg3β by suppressing Gram-negative bacteria through TLR4 signalling Fatima et al ( 2020 ) Swiss albino rats Male (40) 7–9 weeks Chronic Immobilization Stress 20 mg/kg Treatment with melatonin and VitC + Zn alone or in combination significantly restored the altered biochemical parameters and DNA damage of stressed rats to their respective control values. However, the cumulative action of melatonin with VitC + Zn was more effective in alleviating the CIS-induced OS, inflammation, and DNA damage Fernandez-Ortiz et al ( 2020 ) C57BL/6 J Not specified (35) 3 weeks Aging 10 mg/kg/day (orally) Melatonin treatment recovered mitochondrial dynamics altered by aging.…”
Section: Melatonin: Synthesis Secretion Receptors and Functionmentioning
confidence: 99%
“…Another of the effects triggered by COVID-19 is the activation of the inflammasome NLRP3, which sets off the so-called “cytokine storm” (Fatima et al 2020 ), that causes lung inflammation, lesions, and the acute breathing difficulty syndrome (Wu et al 2019 ; Fatima et al 2020 ). Soares et al 2019 confirmed that these mechanisms entail a serious risk of developing MS and a progression towards more serious forms of the disease (Soares et al 2019 ).…”
Section: Melatonin Covid-19 and Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, PH inhibitors stabilised the DNA of lymphocytes and ultimately increased the immune system's resistance. 16 Two randomised, double‐blind clinical trials showed that daily use of melatonin (3 mg/day) could significantly reduce cough rate, dyspnoea, fatigue, C‐reactive protein levels, pulmonary involvement, time of hospitalisation, time of return to baseline health, 9 and improve blood oxygen saturation. 10 Also, a meta‐analysis of three randomised controlled trials confirmed that MLT consumption increases clinical recovery rate, decreases risk of intensive care unit admission, and mortality rate in covid‐19 patients.…”
Section: Why May Melatonin Be a Prolyl Hydroxylase Inhibitor?mentioning
confidence: 99%